Mentors' self‐assessed competence in mentoring nursing students in clinical practice: A systematic review of quantitative studies. Issue 5 (23rd December 2019) - Pramila‐Savukoski, Sari; Juntunen, Jonna; Tuomikoski, Anna‐Maria; Kääriäinen, Maria; Tomietto, Marco; Kaučič, Boris Miha; Filej, Bojana; Riklikiene, Olga; Vizcaya‐Moreno, Maria Flores; Perez‐Cañaveras, Rosa M; De Raeve, Paul; Mikkonen, Kristina
Abstract: Aims and objectives: To examine registered nurses' self‐evaluation of their competence in mentoring nursing students in clinical practice. Background: Clinical mentors have significant roles and responsibility for nursing students' clinical learning. Moreover, the mentors' role is becoming increasingly important internationally, as the role of nurse teachers in mentoring students in clinical practice has declined. However, in most EU countries there are no specific educational requirements for clinical mentors, although they need targeted education to increase their competence in mentoring nursing students. Design: The systematic review of quantitative studies was designed according to guidelines of the Centre for Reviews and Dissemination and PRISMA protocol. Methods: Studies published during 2000–2019 that met inclusion criteria formulated in PiCOS format were systematically reviewed by three independent reviewers. CINAHL (Ebsco), PubMed (MEDLINE), Scopus, ERIC and Medic databases were used to retrieve the studies. Three independent reviewers conducted the systematic review process. The studies were tabulated, thematically compared and narratively reported. Results: In total, 16 peer‐reviewed studies met the inclusion criteria. The studies identified various dimensions of mentors´ competence and associated environmental factors. Generally, participating mentors rated competences related to the clinical environment, mentoring, supporting students' learning processes and relevant personal characteristics fairly high. They also rated organisational practices in their workplaces, resources in the clinical environment and their mentor–student and mentor–stakeholder pedagogical practices, as respectable or satisfactory. Conclusion: The results indicate considerable scope for improving mentors' competence, particularly through enhancing organisational mentoring practices and relevant resources in clinical environments. Relevance for clinical practice: Pedagogical practices of mentors in relations with both students and stakeholders should be enhanced to improve future nurses' learning. This systematic review addresses a gap in knowledge of mentors' self‐evaluated competence that could assist the formulation of effective educational programmes for mentors internationally and improving clinical environments.